Treatment and Survival of Malignant Extracranial Germ Cell Tumours in the Paediatric Population: A Systematic Review and Meta-Analysis - Hulsker, Caroline C. C. (Cancers (Basel), 2021)
SIMPLE SUMMARY: Germ cell tumours are a heterogeneous group of neoplasms and are predominantly midline tumours occurring from birth to late adulthood. Suboptimal outcomes remain for several groups of patients, including adolescents, and patients with extragonadal tumours, high tumour markers at diagnosis or platinum-resistant disease. The aim of our systematic review was to explore survival rates internationally over the past two decades in order to better define future practice and treatment strategies and also to define specific subgroups with inferior outcomes. The results of our systematic review describe the heterogeneous nature of germ cell tumours in different anatomical locations, impacting on stage at presentation, treatment modalities used and survival data. Despite this heterogeneity, subpopulations can be defined which have an inferior survival and where future research and more individualised treatment would help to improve survival. ABSTRACT: Objective: This systematic review and meta-analysis was performed to explore overall survival (OS) and event free survival (EFS) rates internationally over the past two decades and to define specific subgroups with inferior outcomes which may demand different treatment strategies. Methods: The search focused on malignant extracranial germ cell tumours (GCTs) in the paediatric population. The initial database search identified 12,556 articles; 32 articles were finally included in this review, comprising a total of 5095 patients. Results: The studies were heterogeneous, varying from single institution reports to large prospective trials. Older studies, describing eras where non-platinum-based chemotherapy regimens were used, showed clearly worse outcomes. Survival for stage I–II gonadal disease is excellent. On the other hand, patients with an initial alpha-fetoprotein (AFP) > 10,000 ng/mL or kU/L, age > 11 years and stage IV disease confer a survival disadvantage. For testicular disease in particular, lymphovascular invasion and certain histopathological subtypes, such as embryonal carcinoma (EC) and mixed malignant GCTs, survival is poorer. Survival data for sacrococcygeal and mediastinal GCTs show a heterogeneous distribution across studies in this review, independent of year of publication. Patients > 12 years presenting with a mediastinal GCT pose a subpopulation which fares worse than GCTs in other locations or age groups. This is independent of AFP levels, stage of disease or treatment protocol, and these patients may demand a different treatment strategy. Conclusions: This review describes the heterogeneous nature of GCTs in different anatomical locations, impacting on stage at presentation, treatment modalities used and survival data. Despite this heterogeneity, in line with the current developmental biology-based classification system, subpopulations can be defined which have an inferior EFS and OS and where future research and more individualised treatment would help to improve survival.